1986
DOI: 10.1002/ajh.2830230403
|View full text |Cite
|
Sign up to set email alerts
|

Is sickle cell crisis a thrombotic event?

Abstract: Although large vessel thrombi are occasionally reported in patients with homozygous sickle cell disease, the role of intravascular coagulation in typical pain crises is controversial. Therefore, we studied 24 sickle cell patients during and between episodes of pain crisis, using several sensitive tests of hemostasis. Fibrinogen was measured by a clotting assay, beta-thromboglobulin (beta-TG) and fibrinopeptide A (FPA) were quantitated by radioimmunoassay, and protein C was determined by absorbing the zymogen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…7 ¹ 0 . 03 NS and S levels have been reported to be low in both adults (Green & Scott, 1986;Francis, 1988;Hagger et al, 1995) and children (Karayalcin & Lanzkowsky, 1989;El Hazmi et al, 1993;Peters et al, 1994) and could theoretically contribute to a thrombotic tendency. The presence of activated protein C resistance may further exacerbate this tendency (Wright et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…7 ¹ 0 . 03 NS and S levels have been reported to be low in both adults (Green & Scott, 1986;Francis, 1988;Hagger et al, 1995) and children (Karayalcin & Lanzkowsky, 1989;El Hazmi et al, 1993;Peters et al, 1994) and could theoretically contribute to a thrombotic tendency. The presence of activated protein C resistance may further exacerbate this tendency (Wright et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Antithrombin levels have been low (Cacciola et al, 1989;Karayalcin et al, 1984;Onyemelukwe & Jibril, 1992) or normal (Peters et al, 1994;Porter et al, 1993;Hagger et al, 1995) and heparin cofactor II was reduced in one adult study (Porter et al, 1993). Protein C and S levels have also been reduced in most but not all studies (Peters et al, 1994;Hagger et al, 1995;Francis, 1988;Karayalcin & Lanzkowsky, 1989;Green & Scott, 1986;el Hazmi et al, 1993). One study has shown reduced activated protein C resistance (APCR) ratios compared to controls (Wright et al, 1997a) and an association between antiphospholipid antibodies (APA) and SCD has been found in two series of adults (Kucuk et al, 1993;De Ceulaer et al, 1992), though there was no evidence that this conferred an increased thrombotic risk.…”
mentioning
confidence: 99%
“…Considerable evidence now suggests that homozygous SCD (SS) can be considered as a hypercoagulable state, illustrated by increased plasma levels of markers of platelet and coagulation activation both in the steady-state and vasocclusive crises (Green & Scott, 1986;Francis, 1991), and is associated with a high risk of thrombosis which may result from a variety of mechanisms. The aim of this study was to examine if, among other mechanisms, the exposure of phosphatidylserine at the surface of RBCs plays a significant role in vivo.…”
mentioning
confidence: 99%